MAHESHDATTANI’SWHERETHERE’SAWILL:ASTUDYOFREALISTIC DRAMA - Sakhare, Aparna Shailesh; M. B. Gadekar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Drama must be comprehended in light of all the small elements a dramatist displays on stage because it is a visual medium. The dialogue, including monologues and asides, contributes to the overall meaning. Symbols and signs give meaning depth. On a stage, the dramatist brings all of these to life. It is the stage itself that alters the entire comprehension of the drama. In their own right, the stage and stagecraft are forms of art. There are various types of stages that are used in the theatre industry. The most crucial ones are the promenade stage, hippodromes, round stage, open air stage, and proscenium stage. Every stage has its own meaning and staging grammar. The dramatist arranges his actions according to the stage that is in front of him. The type of stage a dramatist chooses to utilise greatly influences the actions in the play. As a result, the stage is essential to theatre and its significance.